Chromium Exposure and Hygienic Behaviors in Printing Workers in Southern Thailand - Somsiri Decharat (Journal of Toxicology)
Objectives. The main objective of this study was to assess the chromium exposure levels in printing workers. The study evaluated the airborne, serum, and urinary chromium levels and determines any correlation between level of chromium in specimen and airborne chromium levels. Material and Methods. A cross-sectional study was conducted with 75 exposed and 75 matched nonexposed subjects. Air breathing zone was measured by furnace atomic absorption spectrophotometer. Serum and urine samples were collected to determine chromium levels by graphite furnaces atomic absorption spectrometer chromium analyzer. Results and Discussion. The printing workers’ urinary chromium levels (6.86±1.93 μg/g creatinine) and serum chromium levels (1.24±1.13 μg/L) were significantly higher than the control group (p<0.001 and p<0.001). Work position, duration of work, personal protective equipment (PPE), and personal hygiene were significantly associated with urinary chromium level and serum chromium levels (p<0.001 and p<0.001). This study found a correlation between airborne chromium levels and urinary chromium levels (r=0.247, p=0.032). A multiple regression model was constructed. Significant predictors of urinary and serum chromium levels were shown in this study. Conclusion. Improvements in working conditions, occupational health training, and PPE use are recommended to reduce chromium exposure.